A novel hyperbaric swimming respirometer allows the simulation of varying swimming depths in fish respirometry studies - Wysujack, Klaus; Marohn, Lasse; Lindemann, Constantin; Illing, Björn; Freese, Marko; Pohlmann, Jan-Dag; Reiser, Stefan; Debes, Paul Vincent; Meskendahl, Laura; Pelster, Bernd; Hanel, Reinhold (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2022)
The understanding of swimming physiology and knowledge on the metabolic costs of swimming are important for assessing effects of environmental factors on migratory behavior. Swim tunnels are the most common experimental setups for measuring swimming performance and oxygen uptake rates in fishes; however, few can realistically simulate depth and the changes in hydrostatic pressure that many fishes experience, e.g. during diel vertical migrations. Here, we present a new hyperbaric swimming respirometer (HSR) that can simulate depths of up to 80 m. The system consists of three separate, identical swimming tunnels, each with a volume of 205 L, a control board and a storage tank with water treatment. The swimming chamber of each tunnel has a length of 1.40 m and a diameter of 20 cm. The HSR uses the principle of intermittent-flow respirometry and has here been tested with female European eels (Anguilla anguilla). Various pressure, temperature and flow velocity profiles can be programmed, and the effect on metabolic activity and oxygen consumption can be assessed. Thus, the HSR provides opportunities to study the physiology of fish during swimming in a simulated depth range that corresponds to many inland, coastal and shelf waters.